PENERAPAN MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) BERBANTUAN MEDIA AUDIO VISUAL BERBASIS KINEMASTER UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV DI SDN 5 TROSO - Rima Pramesti; Hernum Satyanoviani Putri; Syailin Nichla Choirin Attalina (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2023)
ABSTRACT The learning model is a pattern or plan that we can use face-to-face in class which refers to the learning approach used, in which there are teaching objectives, stages in learning activities, learning environment, and class management. Motivation is very influential on student learning outcomes. In order for students' learning motivation to increase, teachers need to choose the right learning model. This study aims to describe and explain the implementation of the Contextual Teaching and Learning (CTL) learning model assisted by audio-visual media in elementary schools and to find out how to increase the learning motivation of fourth grade students at SD Negeri 05 Troso. The type of research used in this research is Classroom Action Research. The location of this research was carried out at SD N 05 Troso Jalan Raya Kudus Jepara, Pecangaan District, Jepara Regency, Central Java Province. the research subjects were fourth grade students at SD N 05 Troso, totaling 25 students. The results of the study concluded that the application of the CTL model assisted by kinemaster-based audio-visual learning media to PPKN material can increase students' learning motivation because the CTL model has a link between learning material and real life so that students can understand concepts and feel involved in learning. With the addition of kinemaster-based animated video learning media students can more easily understand and remember the material. Keywords: CTL (Contextual Teaching and Learning) Model, Audio visual, Kinemaster, Learning motivation